PROSES PEMBUATAN TUTUP GALON DENGAN MATERIAL LOW DENSITY POLYETHYLENE (LDPE) - Maulana Akbar, Andre (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
The gallon cap is one of the most important components for a gallon product in order to maintain the quality of water to keep it high and healthy, made with quality materials In general, the definition of injection molding is the process of forming an object or product from plastic material that is heated and injected into a mold or mold, in principle, it is a tool used to make components from plastic material with a plastic injection machine In the process of making this gallon cap, we know several variables that we can analyze, including cooling / cooling time (5 seconds), how much is the volume of water that comes out (0.1083335 m ^ 3) and the water discharge needed to cool the product (0.0216667 m ^ 3 / s).